1983
DOI: 10.1136/thx.38.8.592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on Vitalograph spirometer readings.

Abstract: ABsTRAcr Spirometric variables were obtained from nine symptomless subjects, who performed forced expiratory manoeuvres with three Vitalograph spirometers at three different ambient temperatures (36.5°C, 24-10C, and -7.3°C) Hutchinson noticed when using his spirometer that subjects had larger vital capacities in summer than winter and therefore decided to correct for the effects of changes in ambient temperature.' He chose to correct for all volumes to 60°F (15°C), which was apparently an average indoor temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In situations where the ambient air temperature is changing rapidly (.3˚C in ,30 min), continuous temperature corrections may be necessary. Spirometer users should be aware of potential problems with testing performed at lower ambient temperatures: 17˚C is the lower limit [55][56][57][58][59][60][61][62][63] for ambient temperature, unless a manufacturer states that their spirometer will operate accurately at lower ambient temperatures. If barometric pressure is not used in calculating the BTPS correction factor, the range of barometric pressures over which the BTPS correction factor is valid must be published by the manufacturer.…”
Section: Btps Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations where the ambient air temperature is changing rapidly (.3˚C in ,30 min), continuous temperature corrections may be necessary. Spirometer users should be aware of potential problems with testing performed at lower ambient temperatures: 17˚C is the lower limit [55][56][57][58][59][60][61][62][63] for ambient temperature, unless a manufacturer states that their spirometer will operate accurately at lower ambient temperatures. If barometric pressure is not used in calculating the BTPS correction factor, the range of barometric pressures over which the BTPS correction factor is valid must be published by the manufacturer.…”
Section: Btps Correctionmentioning
confidence: 99%
“…The rationale for this recommendation is based, in part, on the problems with finite cooling times of gases in volume-type spirometers [55][56][57] and the problems of estimating BTPS correction factors for flow devices [58][59][60]. When a subject performs an FVC manoeuvre, the air leaving the lungs is ,33-35˚C [61,62] and saturated with water vapour.…”
Section: Commentsmentioning
confidence: 99%
“…In a water-seal spirometer the water temperature can be used for correcting inspiratory and expiratory gas volumes. In spirometers equipped with a gas circulation pump the gas temperature at the outlet of the spirometer, or under the spirometer bell, is an acceptable compromise; in spirometers with a common gas inlet and outlet the inspiratory temperature should be measured at that point; the site for expiratory temperatu.re corrections should be carefully chosen within the spirometer [106,149].…”
Section: Temperaturementioning
confidence: 99%
“…Temperature measurements in the mouthpiece showed that in spite of the rapid airflow in a forced expiration, the TD between body and spirometer de creased by about 50%, a finding not ex pected by us and others [2,3,5,14,15]. Cooling proceeds rapidly in the 42-cm tube; the temperature of the expired air at the moment of recording amounted to 85-88% of the ambient temperature.…”
Section: Discussionmentioning
confidence: 80%
“…This also in volved the problem of correct volume cor rection to BTPS [1,4,12,[16][17][18]. The liter ature offers different data concerning the question how to handle temperature cor rection in these usually half-open systems [2,3,6,14,15]. The uncertainty in the answer is reflected in different types of evaluation forms, offering two scales, which so far have been used at the exam iner's discretion.…”
Section: Introductionmentioning
confidence: 99%